Problems of substance addicteds in social life after treatment and practices of social work - Sevin, Ç.; Erbay, E. (Journal of Dependence, 2008)
Addiction affects our society as a significant biopsychosocial problem. However, while numerous studies have been conducted on the biological dimension of addiction, it can be argued that studies on its psychosocial dimension are limited. A process operating within this limitation can only provide temporary and palliative solutions to the problem of addiction. Within this framework, this article will primarily address this multifaceted dimension of substance addiction and discuss what can be done within the social work profession to address this neglected psychosocial dimension. In more detail, the article will provide a brief introduction to substance addiction, followed by a discussion of the problems that arise in social life after treatment and the social work practices that address them. In the social work practices section, individual, family, and community-focused work will be addressed from a multidimensional perspective, focusing on empowerment and teamwork.